1998
DOI: 10.1046/j.1365-2249.1998.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

A vigorous virus-specific CD4+ T cell response may contribute to the association of HLA-DR13 with viral clearance in hepatitis B

Abstract: A strong virus-specific CD4+ and CD8+ T lymphocyte response to hepatitis B virus (HBV) has been associated with viral clearance, but little is known about factors determining the individual's ability to mount such a T cell response. Recently a strong association between the HLA class II allele DR13 and a self-limited course of HBV infection has been described. In the present study of 33 patients with acute hepatitis B we show that individuals carrying HLA-DR13 mount a more vigorous CD4+ T cell response to HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 26 publications
5
62
0
Order By: Relevance
“…This allotype was associated with viral clearance in hepatitis B. 22 Furthermore, in a recent report, Val 86 of the HLA-DR␤ chain was postulated to also determine the response against hepatitis B surface antigen. 23 In this study, HLA-DRB1*1301 and HLA-DR15 alleles were found as the responder alleles, but HLA-DRB1*1302 was associated with nonresponse to hepatitis B surface antigen.…”
Section: Discussionmentioning
confidence: 99%
“…This allotype was associated with viral clearance in hepatitis B. 22 Furthermore, in a recent report, Val 86 of the HLA-DR␤ chain was postulated to also determine the response against hepatitis B surface antigen. 23 In this study, HLA-DRB1*1301 and HLA-DR15 alleles were found as the responder alleles, but HLA-DRB1*1302 was associated with nonresponse to hepatitis B surface antigen.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Although the mechanism of susceptibility to chronic persistent HBV infection is not well clarified, it is known to be influenced by host immunogenetic factors. 8,15 A strong virusspecific CD4 ϩ and CD8 ϩ T-lymphocyte response to HBV has been associated with viral clearance, but comparatively little is known about the factors, which determine the individual' s ability to mount such a T-cell response. Recently, Thursz 6 and Hohler 7 conducted HLA genotyping of adults with persistent HBV infection who had demonstrated spontaneous recovery, and the relative frequency of DRB1*1301 and DRB1*1302 among HLA class II alleles was higher in SC.…”
Section: Discussionmentioning
confidence: 99%
“…Although associations between HLA class I and the outcome of HBV are not consistent, the association between HLA-DR13 and the clearance of HBV in Africans 6 and Europeans 7 has been documented. Moreover, Diepolder et al 8 suggested that the HLA-DR13 allele, a subset of HLA-DR6, might have a beneficial effect on the outcome of HBV infection, as a result of the induction of a more vigorous HBV core-specific CD4 ϩ T-cell response.…”
mentioning
confidence: 99%
“…Viral clearance during acute HCV infection is usually associated with a multispecific CD4 ϩ and CD8 ϩ T cell response, which is weak or undetectable in subjects who do not control the infection (3)(4)(5). Importantly, most chronically infected patients fail to resolve HCV infection after combination therapy with IFN and ribavirin (6)(7)(8).…”
mentioning
confidence: 99%